Bibliometric Analysis of IoT-Driven Smart Agriculture and Irrigation Management Research: Trends, Topics, and Publication Patterns (2019-2024) - Hendrawati, Trisiani Dewi; Narputro, Panji; Wicaksana, Fikri Arif; Suryana, Anang (Universitas Nusa Putra, 2025)
This study explores the bibliometric analysis of research on smart agriculture and IoT-based irrigation management from 2019 to 2024, focusing on trends, topics, and publication patterns. Smart agriculture integrates advanced technologies such as IoT, artificial intelligence (AI), and big data analytics to enhance productivity and sustainability in farming systems. The analysis identifies a steady growth in publications, with a significant spike in 2023, reflecting the increasing global interest in utilizing IoT technologies to address challenges like water scarcity, climate change, and food security. Key topics include IoT-based sensor technologies for soil and water management, precision agriculture, and sustainable farming practices.The study also highlights the role of international collaboration, with countries like India, China, and the United States emerging as central hubs in fostering interdisciplinary research. Major sources such as Lecture Notes in Networks and Systems, AIP Conference Proceedings, and IEEE Access significantly contribute to the dissemination of research findings. Furthermore, the co-occurrence network analysis reveals the dominance of IoT as a central theme, with strong links to related topics like irrigation, soil moisture, and crop management.This research provides valuable insights for researchers, policymakers, and practitioners by identifying critical trends and research gaps, emphasizing the importance of IoT in optimizing irrigation systems, improving efficiency, and promoting sustainable agricultural innovations. These findings support the development of smart agriculture systems that are adaptive to global challenges and resource constraints.